2011
DOI: 10.1007/s11130-011-0257-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Inhibition of Renin and Angiotensin I Converting Enzyme by Polar and Non-polar Polyphenolic Extracts of Vernonia Amygdalina and Gongronema Latifolium Leaves

Abstract: The aim of this study was to determine the in vitro modulation of the renin-angiotensin system by polyphenolic extracts and fractions of two green leafy vegetables, Vernonia amygdalina (VA) and Gongronema latifolium (GL), that are used for food and medicinal purposes. An 80% acetone extract of each leaf was fractionated on silicic acid-packed column to give two main fractions: acetone eluate (flow-through) and ethanol eluate (column-bound), that consist mostly of chlorophyllic and non-chlorophyllic fractions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
1
22
1
1
Order By: Relevance
“…In particular, ACE inhibitory bioactivity has previously been strongly associated with peptide extracts from plant and animal protein sources (De Leo, Panarese, Gallerani, & Ceci, 2009;Guang & Phillips, 2009). Also, as demonstrated in this study, there is a strong correlation between the polyphenolic component of the edible plant product and ACE inhibitory activity which has been demonstrated by other workers in the field (Ajibola, Eleyinmi, & Aluko, 2011;Balasuriya & Rupasinghe, 2011;Yang, Chen, Li, & Tsai, 2007). Inhibition of binding of angiotensin ligands to AT 1 R have been associated largely with plant metabolites of several chemical classes that were extracted by either organic solvents (Caballero-George et al, 2001, 2002a or aqueous media (Huang et al, 2008).…”
Section: Ace Regulation By Dietary Plantssupporting
confidence: 83%
“…In particular, ACE inhibitory bioactivity has previously been strongly associated with peptide extracts from plant and animal protein sources (De Leo, Panarese, Gallerani, & Ceci, 2009;Guang & Phillips, 2009). Also, as demonstrated in this study, there is a strong correlation between the polyphenolic component of the edible plant product and ACE inhibitory activity which has been demonstrated by other workers in the field (Ajibola, Eleyinmi, & Aluko, 2011;Balasuriya & Rupasinghe, 2011;Yang, Chen, Li, & Tsai, 2007). Inhibition of binding of angiotensin ligands to AT 1 R have been associated largely with plant metabolites of several chemical classes that were extracted by either organic solvents (Caballero-George et al, 2001, 2002a or aqueous media (Huang et al, 2008).…”
Section: Ace Regulation By Dietary Plantssupporting
confidence: 83%
“…More importantly is the direct inhibition of renin activity which has been reported to completely block the RAS pathway since renin is known to catalyze the rate-limiting step in RAS (Fitzgerald, 2011). Several synthetic antihypertensive compounds (e.g., captopril, alacepril, lisinopril, enalapril and fosinopril) developed as ACE inhibitors have long been used to inhibit RAS and treat hypertension including other associated cardiovascular disease conditions (Ajibola, Eleyinmi, & Aluko, 2011;Erdmann et al, 2008;Samanarayaka, Kitts, & Li-Chan, 2010). Aliskiren is however, the only available drug therapy for use as renin inhibitor (He, Malomo, Girgih, Ju, & Auko, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of different extracts have shown antioxidant (Igile et al, 1994;Farombi, Owoeye, 2011), antimicrobial (Erasto, Grierson, Afolayan, 2006;Okigbo, Mmeka, 2008), antiparasitic (Tadesse et al, 1993;Ademola, Eloff, 2011;Adiukwu, Amon, Nambatya, 2011), antidiabetic (Akinola et al, 2011;Ong et al, 2011) and antihypertensive (Ajibola, Eleyinmi, Aluko, 2011;Saliu et al, 2011) properties.…”
Section: Introductionmentioning
confidence: 99%